The effect of co-teaching on academic engagement and test anxiety of nursing students of Lorestan University of Medical Sciences - Shourangiz Beiranvand; Afsaneh Beiranvand; Masomeh Foladvandi; Shirin Hasanvand; Yaser Mokhayeri; Mehdi Vatankhah (Mashhad University of Medical Sciences, 2023)
Background: There is valid evidence that supports the impact of active teaching methods on student-related outcomes. One of these active teaching-learning approaches is co-teaching. This study aimed to determine the effect of co-teaching on nursing students' academic engagement and exam anxiety.Methods: This study was conducted with a two-group semi-experimental design. In total, 35 undergraduate nursing students in the second semester of 2021-2022 at Lorestan University of Medical Sciences, who had chosen the Fundamental of Nursing course, was selected by whole enumeration based on the inclusion criteria. Teaching was provided conventionally for the control group (n =18) while co-teaching was done for the intervention group (n = 17). The participants completed the academic engagement scale and the exam anxiety scale at two points: the end of the 10th session and the end of the 20th week. Data were analyzed using t-test, paired t-test, and chi-square in Stata 17 software.Results: The results showed that the collaborative teaching approach, compared to conventional teaching, had no significant difference in the students' average score of academic involvement and test anxiety.Conclusion: The co-teaching method did not show any difference in the variables of academic involvement and test anxiety compared to conventional teaching. More studies are suggested to plan co-teaching methods.